Agglomeration Effects on Employer-Provided Training: Evidence from the UK - Giorgio Brunello; Francesca Gambarotto (Center for Economic Studies and ifo Institute (CESifo), 2004)
Recent empirical evidence suggests that the density of local economic activity - measured as the number of employees per squared kilometer - positively affects local average productivity. In this paper we use British data from the European Community Household Panel to ask whether local density affects employer-provided training. We find that training is less frequent in economically denser areas. We explain this result as the outcome of the interaction between the positive pooling effects and negative poaching and turnover effects of agglomeration. The size of the negative effect of density is not negligible: when evaluated at the average firm size in the local area, a 10 percent increase in density reduces the probability of employer-provided training by 0.07, more than 20 percent of the average incidence of training in the UK during the sample period.
Keywords: 330; training; spatial economics; Britain